A conceptual analysis of farmers’ willingness to accept the environmental protection model - Afroz, Rafia; Fauzi, Puteri Farhana (Kaav Publications, 2018)
Malaysia is one of the growing newly industrialized countries. In the way of economic development, the agricultural sector in Malaysia has contributed significantly to the gross domestic product (GDP). This research is intended to connect the potential of agricultural production and direct them to contribute to the Malaysian economy. However, the contribution of agriculture has been declining as 8.9% in 2000 and 8.2% in 2005. Because farmers in Malaysia has to face a number of barriers to adaptation, such as resource constraint, socio-cultural barriers and institutional barriers. To overcome the situation, we need to find alternative solutions. This study aims to discuss the barriers faced by farmers in Malaysia and to propose an integrated waqf environmental protection model in order to address the barriers effectively. This study also tries to develop a theoretical framework to analyze how different factors affect farmers’ willingness to accept the proposed model. This study will help policymakers to plan more effective policies to improve the potential role of waqf to mitigate barriers to adaptation and sustainable livelihoods of rice farmers in Malaysia. While the author's knowledge, the idea of environmental waqf is a relatively new concept and today certainly need a lot of discussion.